5-4h=8+4h-3

Simple and best practice solution for 5-4h=8+4h-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-4h=8+4h-3 equation:



5-4h=8+4h-3
We move all terms to the left:
5-4h-(8+4h-3)=0
We add all the numbers together, and all the variables
-4h-(4h+5)+5=0
We get rid of parentheses
-4h-4h-5+5=0
We add all the numbers together, and all the variables
-8h=0
h=0/-8
h=0

See similar equations:

| 6x=5x*8+102 | | 28=2x+5x | | 28=2x+5 | | 4n+22+5n+32=180 | | 5x2–20=0 | | 5c-(3c+8)=7 | | 4n+22=5n+32 | | -8(4r-5=-30+2r | | (5x-2)=54 | | x/15=18/20 | | 3=r/105 | | 5x+78=10x-7 | | 10+0.5x=3 | | 7x-25=40 | | 3(4x+1)+2(6x–1)=13 | | 2/5=70/x | | 4b=3b+b | | 4n-10n^2=0 | | x+14.5=16 | | 3.5x+2.5=2.5+3 | | 2x-63=-x^2 | | v/3-33=-25 | | (8x+93)=117 | | r-19/10=5 | | 0.04(y-4)+0.06y=-0.12y-0.01(30) | | 5(4x–3)=6(2x+5)–5. | | (8x+88)=104 | | z+43/10=6 | | -4a-4=7/4a-3 | | 63=9(t-85) | | m/6+31=33 | | x=x5+78 |

Equations solver categories